Asuhan Kebidanan Komprehensif pada Ny. M Umur 27 Tahun G3P1A1 di Klinik Tri Karya Bandungan - Wijayanti, Lilis; Widyaningsih, Ari (Universitas Ngudi Waluyo, 2024)
The open umbilical cord care technique for newborns is a technique that frees the umbilical cord openly without giving gauze or alcohol. The purpose of the open umbilical cord care technique is to prevent infection of the newborn's umbilical cord and to improve the process of separating the newborn's umbilical cord from the stomach. By using open umbilical cord care techniques for newborns, this will make the process of draining and releasing the umbilical cord easier. This happens because the umbilical cord in newborns is exposed to air. In the community, babies are still often found with the condition of the umbilical cord with gauze that is still sticky to the umbilical cord and the umbilical cord that smells which is a characteristic of the occurrence of infection in the umbilical cord of newborns, which is caused by mothers not daring to change the umbilical cord dressing. Conditions like this can occur, one of which is caused by the knowledge of mothers who have just given birth. Therefore, it is health counseling regarding methods of open umbilical cord care techniques in newborns. Where this is deliberately intended for mothers. The research method used in this study is a literature review. Articles were searched on Google Scholar and Science Direct with the keywords open cord care, cord detachment, newborns, benefits of open cord. The selected articles are Indonesian articles which can be accessed in full text in pdf format. The research results show that by using open umbilical cord care techniques in newborns, this will facilitate the process of drying and also releasing the umbilical cord. This happens because the umbilical cord in newborns is exposed to air. Within twenty-four hours, there will be a change in the color of the center of the rope, that is, from white to brown or black, and the center of the rope in the baby becomes stiff and dry. Umbilical cord care in newborns if done in the right way, the umbilical cord in newborns will dry and fall off within five to seven days without any complications in the baby's umbilical cord. Improper care of the umbilical cord will slow down the discharge of the umbilical cord, and can also increase the risk of infection. .In addition, through health counseling regarding techniques for caring for the umbilical cord in newborns, it shows an increase in the knowledge of the counseling participants regarding the benefits obtained using the open umbilical cord care method for infants. Abstrak Angka Kematian Ibu (AKI) menjadi salah satu indikator penting dari derajat kesehatan masyarakat. AKI menggambarkan jumlah wanita yang meninggal per100.000 kelahiran hidup (KH), dari suatu penyebab kematian terkait dengan gangguan kehamilan atau penanganannya (tidak termasuk kecelakaan atau kasus insidentil) selama kehamilan, melahirkan dan dalam masa nifas (42 hari setelah melahirkan) sehingga dilakukan asuhan komprehensif untuk mencegah kematian ibu selama kehamilan, persalinan dan nifas (Profil Kesehatan Indonesia, 2018). Angka Kematian Neonatal di Kabupaten Semarang Tahun 2017 sebesar 5.44 per 1.000 KH (73 kasus), dengan penyebab tertinggi adalah kelahiran dengan Berat Bayi Lahir Rendah, asfiksia, kelainan kongenital dan penyebab lainnya antara lain penyakit jantung bawaan, sepsis dan lain- lain. Angka Kematian Neonatal Tahun 2017 lebih rendah dibandingkan Tahun 2016 (Profil Kesehatan Kabupaten Semarang, 2017). Deskriptif dan jenis penelitian deskriptif yang digunakan adalah studi penelaahan kasus (Case Study), yakni dengan cara meneliti suatu permasalahan melalui suatu kasus yang terdiri dari unit tunggal. Unit tunggal disini dapat berisi satu orang, sekelompok penduduk yang terkena suatu masalah. Setelah melakukan asuhan telah memberikan asuhan kebidanan secara Komprehensif mulai dari Ibu Hamil, Bersalin, Nifas, Bayi dan hasilnya hamil dengan normal, bersalin dengan normal, bayi dengan normal, dan sampai dengan KB. Tidak terdapat kesenjagan antara teori dan kasus pada Asuhan Komprehensif kebidanan pada Ny. M dan By. Ny. M di Klinik Tri Karya.